"Why Are You Concerned?" A Consideration of Turn Distance and the Organization of the Interrogative Series in "Wellness Check" Calls to a University Police Department. Issue 7 (2nd October 2016) - Kevoe-Feldman, Heidi
Abstract : This study focuses on a type of request referred to as a "wellness check, " commonly made to a large university police department located on the east coast of the United States. A "wellness check" occurs when a loved one calls with concerns about a person they believe to be in distress or in need of assistance. The focus of the analysis considers how call-takers' positioning of the "what's your concern" question within the interrogative series, vis-à-vis the reason for calling (e.g., turn distance from the reason for calling), has consequences for the type of information call-takers are able to extract from callers about their concerns. Findings suggest that the position of this inquiry within the interrogative series has implications for how call-takers solicit callers' collaboration toward building a report that can later be communicated to responding officers.